How do we keep proper level of content diversity: The influence of the gigantic platform on content diversity - Changjun Lee; Junseok Hwang (International Telecommunications Society (ITS), 2014)
This paper aims to study the origin of the role of diversity in the new ICT ecosystem, and show how the gigantic platform influences on the level of diversity of content. Using genetic algorithm, it makes possible to reflect the new ICT ecosystem and experiment how the system is changing content diversity. The novelty of this method is introducing the new measurement of content diversity which is from the genotype diversity in artificial evolution area. The result of the experiments shows that the exposed diversity of content seems to be maintained, but the genuine diversity of content is decreased gradually and disappeared in the end. In addition, the average performance is also decreased in the long run. This clearly shows that decreasing diversity of content is not perceived as much of problem for the present; however, it will generate a big problem if the regulator does nothing to solve this problem. Therefore, this paper insists that diversity, which is reservoir of creativity and the power of sustainable growth in the new ICT ecosystem, must be kept properly and this is the very first step for settling the new standard. This might contribute for policy makers to give them wisdom by which criteria they can look at the reality in this rapidly changed technology and business environment and we hope more empirical studies are coming with it.
Keywords: 330; content diversity; platform; ICT ecosystem; sustainability